2007
DOI: 10.1177/039139880703000206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Metabolic Syndrome in Hemodialysis

Abstract: Background Recently, the concept of the metabolic syndrome (MS) has emerged in an effort to group and study as a whole several cardiovascular risk factors. The definition of the metabolic syndrome requires the presence of 3 or more of the following parameters: high blood pressure (≥30/85), waist circumference >102 cm in men and >88 cm in women, HDL<50 mg/dL in men and <40 mg/dL in women, serum triglycerides >150 mg/dL and fasting blood glucose ≥110 mg/dL. Objectives: To investigate the prevalence of the MS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 7 publications
3
20
2
Order By: Relevance
“…[1][2][3][4][5] In this study, the prevalence was 59.5%, which is consistent with high prevalence of MeS in general Iranian population (50.8%). 24 Relatively little is known about the precise causes of such a high prevalence.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[1][2][3][4][5] In this study, the prevalence was 59.5%, which is consistent with high prevalence of MeS in general Iranian population (50.8%). 24 Relatively little is known about the precise causes of such a high prevalence.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of MeS in HD patients is reported from 40% to 60%. [1][2][3][4][5] This syndrome is considered as a significant risk factor for cardiovascular disease, mortality, and chronic kidney disease in the general population. [6][7][8][9] MeS also is a predictive parameter of mortality for HD patients, 10,11 and predicts hospitalization in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the prevalence of MetS was 38.2%, which is lower than in the other reported study; this is likely because the mean HD duration in our study was 5.8 years [17, 18]. In 2011, a study conducted in Riyadh, Saudi Arabia in ESRD patients on HD showed that 58% had MetS [19].…”
Section: Discussioncontrasting
confidence: 60%
“…This knowledge obligates a methodical approach to diabetes screening and management that begins with a patient's initial pretransplantation visit, continuing Finally, screening and management of two additional risk factors for NODM in kidney recipients should be commenced during pretransplantation evaluation. First, because metabolic syndrome is common in patients with chronic kidney disease (34), screening for its components should be performed (19) to permit intervention as appropriate. Second, for HCV-infected candidates, the pretransplantation setting provides an opportunity to attempt viral clearance with interferon therapy.…”
Section: Detection and Management Of Diabetes In The Transplant Settingmentioning
confidence: 99%